Diamine-Appended Metal Oxide Framework Materials for Thermal-Swing Ad- and Desorption of Carbon Dioxide at Ambient Conditions - Maharjan, Kamal K.; Jørgensen, Philip B.; Rezaei, Mohsen; Johnson, Matthew S. (Frontiers in Environmental Chemistry, 2022)
Carbon dioxide is a waste product of human metabolism that is unwanted in the indoor atmosphere. Here we test advanced materials that could be used to pump away carbon dioxide and thereby improve indoor air quality. Metal-organic framework (MOF) structures have a variety of properties that make them attractive for direct air capture (DAC) of CO 2 . In this study, Mg 2 (dobpdc4- = 4,4-dioxidobiphenyl-3,3-dicarboxylate) and m-2-m-Mg 2 (dobpdc) were evaluated for their ability to adsorb and desorb CO2 at ambient atmospheric conditions via a thermal swing. The Mg 2 (dobpdc) sample did not show appreciable interaction with CO2 in contrast to the diamine-appended version. The molar occupancy of CO2 on the active sites of m-2-m-Mg 2 (dobpdc)(m-2-m = N,N-dimethylethylenediamine) during adsorption and desorption was in the range of 5.6 to 11.8 %. These experiments showed the rapid ad- and de-sorption of CO2 by the MOF. Relative humidity was seen to be an important variable and the performance of the tested structures decreased slightly after several cycles of use.